2020
DOI: 10.1515/cmam-2019-0115
|View full text |Cite
|
Sign up to set email alerts
|

Instance-Optimal Goal-Oriented Adaptivity

Abstract: We consider an adaptive finite element method with arbitrary but fixed polynomial degree p ≥ 1, where adaptivity is driven by an edge-based residual error estimator. Based on the modified maximum criterion from [Diening et al, Found. Comput. Math. 16, 2016], we propose a goal-oriented adaptive algorithm and prove that it is instance optimal. Numerical experiments underline our theoretical findings.Date: July 31, 2019. 2010 Mathematics Subject Classification. 65N30, 41A25, 65N12, 65N50. Key words and phrases. A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 27 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…In this section, we discuss the least-squares finite element methods for the second-order elliptic equation with an H −1 righthand side. Such a problem appears in many situations, for example, in the goal-oriented a posteriori error estimate [31].…”
Section: Extension To Least-squares Finite Element Methods With H −1 ...mentioning
confidence: 99%
“…In this section, we discuss the least-squares finite element methods for the second-order elliptic equation with an H −1 righthand side. Such a problem appears in many situations, for example, in the goal-oriented a posteriori error estimate [31].…”
Section: Extension To Least-squares Finite Element Methods With H −1 ...mentioning
confidence: 99%
“…However, all these works employ the so-called Dörfler marking strategy proposed in [Dör96] to single out elements for refinement. Moreover, for the 2D Poisson problem, it has recently been shown that a modified maximum criterion does not only lead to optimal convergence rates, but even leads to instance optimal meshes [DKS16, KS16,IP20]. As the focus comes to other marking strategies, only plain convergence results are known and the essential works are [MSV08,Sie11].…”
Section: Introductionmentioning
confidence: 99%